Humoral Response to SARS-COV-2 Vaccination in Patients with Multiple Sclerosis and Neuromyelitis Optica Spectrum Disorder: A Real-World Study - Jorge Millán-Pascual; Gabriel Valero-López; Francisca Iniesta-Martinez; Maria Fuensanta Hellin-Gil; Judith Jimenez-Veiga; Isabel Alejandra López-Tovar; Ana Morales-Ortiz; José. E. Meca-Lallana (Neurology and Therapy, 2023)
Abstract Introduction The risk of SARS-CoV-2 infection or severe coronavirus disease 2019 (COVID-19) has been shown to increase in patients with multiple sclerosis (MS). Vaccination is recommended in this patient population, and the effect of disease-modifying treatments (DMTs) on response to vaccination should be considered. Methods This prospective, observational, cross-sectional study investigated humoral response after COVID-19 vaccination as well as possible predictors for response in patients with MS and other neuroinflammatory diseases who received DMTs in routine clinical practice in Spain. Responses were compared versus those seen in healthy controls. Results After vaccination against COVID-19, most patients with MS developed an immune response comparable to that of healthy individuals. However, approximately half of patients receiving a sphingosine-1-phosphate modulator (SP1-M, fingolimod or siponimod) or a B-cell-depleting agent (aCD20, ocrelizumab or rituximab) did not develop protective antibodies, although patients receiving other DMTs had humoral immune responses comparable to healthy controls. Lymphocyte count was not associated with reduced humoral response in patients receiving an SP1-M or aCD20, whereas, in patients receiving an aCD20 or SP1-M, older age was associated with lower anti-SARS-CoV-2 spike protein immunoglobulin G antibody levels. Conclusions Treatment with aCD20 or SP1-M therapies appears to be associated with a lower humoral response to vaccines against SARS-CoV-2. Vaccination prior to initiation of these DMTs should be recommended whenever possible.